2018
DOI: 10.1155/2018/7676058
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Water Use Efficiency of Sorghum [Sorghum bicolor (L.) Moench] Grown under Different Nitrogen Applications in Sudan Savanna Zone, Nigeria

Abstract: Nitrogen (N) is an essential nutrient for sorghum growth and development but often becomes limiting due to low availability and loss. The effects of N fertilization on water use efficiency (WUE) and physiological and yield traits of sorghum were investigated in two locations over two cropping seasons (2014 and 2015) in the Sudan Savanna zone of Nigeria. Three sorghum varieties were evaluated under six (6) N-levels (0, 20, 40, 60, 80, and 100 kg ha−1) at a constant phosphorus and potassium level of 30 kg ha−1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 24 publications
7
28
0
1
Order By: Relevance
“…Our results show that the water-use efficiency increased in the second cropping period compared with the first in both crops studied (Figure 8a,b). Better performance in this parameter in sorghum plants confirms that this cereal is well adapted to situations of low water supply, using available water more efficiently in its metabolic processes (Ajeigbe, Akinseye, Ayuba, & Jonah, 2018). Increases in water-use efficiency were observed in sorghum biomass (Enciso, Jifon, Ribera, Zapata, & Ganjegunte, 2015), saccharine sorghum (Curt, Fernandez, & Martinez, 1995) and grain sorghum (Jabereldar, Naim, Abdalla, & Dagash, 2017) in conditions of low water availability.…”
Section: Discussionmentioning
confidence: 76%
“…Our results show that the water-use efficiency increased in the second cropping period compared with the first in both crops studied (Figure 8a,b). Better performance in this parameter in sorghum plants confirms that this cereal is well adapted to situations of low water supply, using available water more efficiently in its metabolic processes (Ajeigbe, Akinseye, Ayuba, & Jonah, 2018). Increases in water-use efficiency were observed in sorghum biomass (Enciso, Jifon, Ribera, Zapata, & Ganjegunte, 2015), saccharine sorghum (Curt, Fernandez, & Martinez, 1995) and grain sorghum (Jabereldar, Naim, Abdalla, & Dagash, 2017) in conditions of low water availability.…”
Section: Discussionmentioning
confidence: 76%
“…These reductions showed that intercrop competition occurred for N instead of supplementation of N by the associated legume. Abd El-Lattief [43] and Ajeigbe et al [44] observed that increasing N levels increased grain yield of sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…12.17 N,Long 8.65 E, 473 m asl) and Teaching and Research farm, Bayero University Kano (BUK) (Lat.11.98 N and Long 8.43 E, 508 m asl). The agronomic data such as dates of sowing, flowering and maturity), yield and final biomass for two (early-ICSV-400 and medium-Improved Deko) sorghum varieties were obtained from several field experiments conducted in the context of larger varietal characterization trials under integrated soil fertility management (Ajeigbe et al 2018a(Ajeigbe et al , 2018b. The soil of the experimental sites (Minjibir and BUK) were characterized as slightly acid to neutral (pH 5.5-7), and was low in plant available nitrogen, phosphorus and calcium, had low organic carbon content (OC 1%).…”
Section: Experimental Data For Model Calibration and Evaluationmentioning
confidence: 99%
“…Sorghum has been found as water efficient crop transforming available water more into dry matter than most other C 4 crops (e.g., maize) (Dercas and Liakatas 2007) and the crop is able to utilize water as deep as 270 cm soil depth (Mishra, Thakur, and Singh 2015). Its production is not only limited by rain shortage and nitrogen nutrition, but by the poor resource base, low input use and returns and rapid population increases (MacCarthy et al 2010;Ajeigbe et al 2018aAjeigbe et al , 2018b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation